2021
DOI: 10.1002/adbi.202101019
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Associated Protrusion Fluctuations as a Signature of Cancer Invasiveness

Abstract: The generation of invasive fluctuating protrusions is a distinctive feature of tumor dissemination. During the invasion, individual cancer cells modulate the morphodynamics of protrusions to optimize their migration efficiency. However, it remains unclear how protrusion fluctuations govern the invasion of more complex multi‐cellular structures, such as tumors, and their correlation with the tumor metastatic potential. Herein, a reductionist approach based on 3D tumor cell micro‐spheroids with different invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…After 1 d of culture, the thickness of the substrates decreased to ~15 μm ( Figure S4 ). Despite the decrease in substrate thickness over 5 d of cell culturing, the substrate thickness remained in the acceptable range for avoiding the cell sensing of the underneath coverslip glass; because the MCF7 cell protrusion length was ~7 μm [ 36 ]. The interface of the substrates was relatively flat.…”
Section: Resultsmentioning
confidence: 99%
“…After 1 d of culture, the thickness of the substrates decreased to ~15 μm ( Figure S4 ). Despite the decrease in substrate thickness over 5 d of cell culturing, the substrate thickness remained in the acceptable range for avoiding the cell sensing of the underneath coverslip glass; because the MCF7 cell protrusion length was ~7 μm [ 36 ]. The interface of the substrates was relatively flat.…”
Section: Resultsmentioning
confidence: 99%
“…[108] This work paves the way for optofluidic-driven analysis of micromechanical events, highly relevant in living tissues and cancer, [14] where fluctuations of cancer-associated protrusions represent a clear signature of cancer invasiveness. [109] These results show how the combination of live cell imaging in microfluidic settings can take advantage of optofluidic strategies for real-time detection of cellular shape, composition, and mechanics, where a wide range of cancer cell responses and premetastatic events can be monitored with unprecedented efficacy. The tracking of those signatures can be further combined with studies on drugs of interest, boosting the discovery of effectiveness in much more complex and in vivo-like responses.…”
Section: Interfacing Photonics With Microfluidic Chips-optofluidicsmentioning
confidence: 90%
“…We could observe that cancer cells in the presence of RBCs, especially from metastatic cancer patients, change cell morphology, transitioning from a rounded shape to a more mesenchymal cell type with lamellipodia-like protrusions, key membrane structures involved in chemo-sensing and migration [31][32][33] and commonly associated with increased metastatic potential 34 . Furthermore, we also observed that tumour cell lines show enhanced migratory and adhesive capabilities after having direct contact with RBCs from cancer patients.…”
Section: Discussionmentioning
confidence: 99%